A preliminary report on adjuvant analgesic efficacy of HANS in opioid tolerant patients with cancer pain - Li, Xiaomei; Zhu, Jianhua; Li, Pingping; Zhu, Guangqing; Wu, Xiaoming; Chen, Huoming; Zhao, Huixia; Wang, Wei; Zhang, Ying; Xiao, Wenhua; Liu, Duanqi (Chinese Journal of Cancer Research, 2014)
Objective: To observe the adjuvant analgesic efficacy of Han’s Acupoint Nerve Stimulator (HANS) in opioid tolerant patients with cancer pain. Methods: A prospective non-controlled study was conducted. Opioid tolerant patients with cancer pain were enrolled and treated with both routinely analgesics and adjuvant HANS (2/100 Hz for 30 min/d, 5 d on and 2 d off for two weeks). Cancer pain, quality of life (QOL), anxiety and depression were assessed before enrollment and on d 8 and d 15 with the BPI-C, EORTC QLQ-C30, and self-rating anxiety scale (SAS)/self-rating depression scale (SDS), respectively; the therapeutic frequency of breakthrough pain (BP) and daily opioid dose were also recorded. Results: Totally 47 patients meeting the inclusion criteria participated in this study; 43 patients completed the two-week treatment and assessment. The mean scores of patient’s “worst” and “least” pain intensity assessed with BPI-C decreased significantly on d 8 and d 15; the therapeutic frequency of BP also significantly decreased; but the average daily dose of opioids did not change significantly. For the nine symptoms in EORTC QLQ-C30 assessment, the mean scores of pain, fatigue, constipation and insomnia were significantly lower on d 8 and d 15 compared with baseline; the mean scores of the overall health status, nausea/vomiting and the incidence rates of both anxiety and depression also decreased significantly on d 15. Conclusions: To opioid tolerant patients with cancer pain, adjuvant treatment with HANS could improve pain release and patients’ QOL by decreasing the severity of pain, fatigue, constipation, insomnia and other concomitant symptoms; it could also decrease the incidence rates of anxiety and depression.